2012
DOI: 10.1159/000335658
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Physical Mapping of Two Classes of 5S rDNA in the Genomes of <i>Gymnotus sylvius</i> and <i>G. inaequilabiatus</i> (Gymnotiformes, Gymnotidae)

Abstract: The nucleotide sequences of the 5S rRNA multigene family and their distribution across the karyotypes in 2 species of Gymnotiformes, genus Gymnotus (G. sylvius and G. inaequilabiatus) were investigated by means of fluorescence in situ hybridization (FISH). The results showed the existence of 2 distinct classes of 5S rDNA sequences in both species: class I and class II. A high conservative pattern of the codifying region of the 5S rRNA gene was identified, contrasting with significant alterations detected in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…In the species in which it was mapped, the markings were species-specific, 4,33,42 which was also the case for the three species analyzed in this study.…”
Section: Discussionmentioning
confidence: 58%
“…In the species in which it was mapped, the markings were species-specific, 4,33,42 which was also the case for the three species analyzed in this study.…”
Section: Discussionmentioning
confidence: 58%
“…inaequilabiatus, G . pantherinus) have been studied previously [Scacchetti et al, 2011[Scacchetti et al, , 2012.…”
Section: Sampling and Preparation Of Mitotic Chromosomesmentioning
confidence: 99%
“…U2 snDNA probes corresponded to a 150-bp segment containing partial sequences of the U2 snRNA gene. The 5S rDNA probe included 120 bp of the 5S rRNA gene and 229 bp of the nontranscribed spacer [Scacchetti et al, 2012].…”
Section: Repetitive Probes and Fish Experimentsmentioning
confidence: 99%
“…In neotropical fish, most comparative cytogenetic studies have focused on repetitive sequences of rRNA genes, which have shown that chromosome structures are very dynamic in relation to the number and location of rRNA clusters [Ferro et al, 2001;Kavalco et al, 2004;Scacchetti et al, 2012]. Otherwise, there is a great lack of studies for a detailed knowledge of the organization and distribution of histone genes within the fish genomes.…”
mentioning
confidence: 99%